Using different carbohydrates in prenatal life, growing and mid-lactation can affect lactation persistency in first lactating sheep - Ledda A.; Lunesu M.; Ledda M.; Spanu G.; Fenu A.; Mazza A.; Fancello F.; Cannas A.; Atzori A.S. (Innovation for sustainability in sheep and goats, 2019)
Improving milk production by using digestible fiber rich by-products would increase production efficiency and reduce environmental impact of sheep production. We hypothesized that prenatal and early life exposure to either starch from corn grain or highly digestible fiber from beet pulps and soy hulls would affect sheep response to the same feeds in mid-lactation. Two groups of 12 Sarda ewes each were exposed during the last two months of the prenatal life to two different isoproteic diets (one per group) and then fed the same diet during their growing phases and their first pregnancy. The diets were one glucogenic, being rich in starch from corn grains (S; 21% of starch and sugars, DM basis), the other lypogenic, being rich in digestible fiber from soy hulls and beet pulps (F; 9% of starch plus sugars, DM basis). In early lactation (until 54 DIM) all the 24 ewes received the same glucogenic S diet to support the lactation peak. From 55 to 160 days in milk (DIM) the ewes with S and F background, homogeneous per yield and BCS, were split to S or F total mixed rations (with 24%, S, and 13%, F, of starch plus sugars, DM basis), creating 4 groups of 6 ewes each: SS, SF, FS and FF based on the dietary sequence applied between prenatal life and parturition and between mid-lactation to the end of the experiment. Milk yield and composition were measured each 10 days and BCS every two weeks. Milk yield and composition were compared by using the PROC MIXED procedure of SAS for repeated measurements. At 55 DIM, milk production was (mean ± SE) 1.592 ± 0.096 kg/d per ewe and BCS was 2.85 ± 0.15. The S diet provided during early life and until parturition favored the production of fat and protein corrected milk (FPCMY) and a higher persistency on ewes fed the F diet compared to those fed the S diet during their mid lactation (1.483 ± 0.180 vs.1.143 ± 0.198 kg/d for SF vs. SS, respectively; P<0.05), whereas ewes with F background had no different milk persistency with both mid-lactating diets (1.269 ± 0.198 vs 1.198 ± 0.180 kg/d for FS and FF, respectively). BCS did not differed among groups at 160 DIM. On ewes exposed to S early in life, the use of F in mid-lactation was significantly associated to higher FPCMY compared to S ewes after 110 DIM (P=0.05). The positive effects of the exposure to glucogenic diets in early life suggest to investigate the hormonal and metabolic mechanisms underlying these results.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)